1995
DOI: 10.1093/jac/35.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of vancomycin and high-level gentamicin resistance genes on the same plasmid in a clinical isolate of Enterococcus faecalis

Abstract: A transferable 55-MDa plasmid which encoded resistance to both vancomycin and high concentrations of gentamicin was identified in a clinical isolate of Enterococcus faecalis. The plasmid hybridized with probes for the vanB and aac6'aph2" resistance genes. This is the first report of linkage of glycopeptide and high-level aminoglycoside resistance genes in an Enterococcus sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…Transfer of vancomycin resistance from clinical isolate C68 to E. faecium GE-1 is associated with the transfer of ampicillin and tetracycline resistances and with acquisition of an approximately 130-160 kb segment of chromosomal DNA (Carias et al, 1998). In E. faecalis E93\268 and E. faecium 654 clinical isolates, resistance to vancomycin was found to be associated with a vanB gene cluster carried by plasmids pIP834 and pIP835, respectively (Woodford et al, 1995a, b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transfer of vancomycin resistance from clinical isolate C68 to E. faecium GE-1 is associated with the transfer of ampicillin and tetracycline resistances and with acquisition of an approximately 130-160 kb segment of chromosomal DNA (Carias et al, 1998). In E. faecalis E93\268 and E. faecium 654 clinical isolates, resistance to vancomycin was found to be associated with a vanB gene cluster carried by plasmids pIP834 and pIP835, respectively (Woodford et al, 1995a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus faecalis E93\268, isolated from a blood culture at 0002-4032 # 2000 SGM Addenbrooke's Hospital in Cambridge, UK, was resistant to high concentrations of gentamicin (MIC 2000 mg l − ") and expressed the VanB phenotype, i.e. resistance to vancomycin (MIC 32 mg l − ") and susceptibility to teicoplanin (MIC 1 mg l − ") (Woodford et al, 1995a). E. faecium 654 was isolated in the renal unit of the Queen Elizabeth Hospital in Birmingham, UK, and is also of the VanB type (Woodford et al, 1995b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,7 High level aminoglycoside resistant Enterococci often have plasmids, which carry determinants encoding resistance to other antibiotics. It is notable that Woodford et al demonstrated linkage of the vancomycin resistance and high-level gentamicin resistance genes on the same plasmid in a clinical isolate of E. faecalis and the presence of the gentamicin resistance gene on a variety of physically distinct conjugative and non-conjugative plasmids in E. faecalis facilitates the wide dissemination of multidrugresistant strains with characteristics that allow them not only to persist but also to spread.…”
Section: Discussionmentioning
confidence: 99%